How clicktivism enables moral licensing : the effects of social observability and impression management on subsequent prosocial behaviour - Tan, Si Jin (2019)
In recent years, token acts of online support, also known as Clicktivism, have received much criticism for decreasing subsequent prosocial behaviour. However, it is unclear when and why individuals perform less prosocial behaviour after engaging in Clicktivism. Participants in the present study were assigned to one of three experimental groups: reading an article without signing a petition, or signing a public or private online petition. Moral licensing effects were observed among those who had signed a petition, such that they were less likely to donate to the same social cause. The social observability of an act of Clicktivism was found to have an influence on subsequent prosocial behaviour in which moral licensing effects were more pronounced in the private condition, as compared to those who did not sign a petition. Lastly, in the public condition, perceived success in impression management was introduced to explain the effects of moral licensing. Those with low perceived success of a public act of Clicktivism in impression management were less likely to donate, as compared to those with high perceived success. This study also builds on existing moral licensing literature and seeks to address the ineffectiveness of Clicktivism.